Developing a safety culture framework for the mining industry in malaysia - Siti Noraishah, Ismail (2024)
Mine disasters lead to fatalities as well as detrimental effects on our economy. These days, safety culture is important as a means of preventing mining accidents or disasters. Three main dimensions are required to construct a good safety culture: psychological, situational, and behavioral dimensions. Moreover, the influencing factors for each dimension are critical to be investigated and understood for the mining industry. Malaysia has been blessed with various minerals, such as gold, tin ore, bauxite, and iron ore. Fortunately, to date, no large-scale mining disaster has occurred in Malaysia. However, a lack of study on the safety culture in the Malaysian mining industry was discussed. According to the Malaysian Social Security Organization, there were 130,000 mine workers in the year 2021 in Malaysia, with increasing mining accidents reported. Therefore, the objectives of this study were to investigate the influencing factors of psychological, situational, and behavioral safety culture and develop a safety culture framework for the Malaysian mining industry. This study applied an exploratory sequential mixed method. The study started with a preliminary study that involved an extensive literature review called (i) Systematic Literature Review and (ii) interview sessions with volunteered mining experts. Based on the interview session, all experts agreed that safety culture awareness and practices in Malaysia are still low (less than 50% for small-scale mining) and can reach up to 70% for large-scale mining. This gap needs to be closed, and the safety culture framework is demanding for Malaysia. The study was continued with Delphi I and Delphi II, with the involvement of 21 and 18 mining experts as respondents, respectively. These respondents consisted of mining consultants, government enforcers, mine owners, mining managers, academicians, The Delphi I started with the open-ended interview session, which was conducted via Google Meet from March to May 2021. The objective of the interview session was to investigate the influencing factors of psychological, situational, and behavioral safety culture among 21 mining experts. All the qualitative findings were analyzed using thematic analysis. There are 5, 10, and 9 important influencing factors obtained for the psychological, situational, and behavioral dimensions. For Delphi II a safety culture questionnaire survey was validated by a validator and distributed to the mining experts. Based on Delphi II, a strong consensus was reached, resulting in 64.81%, 73.15%, and 73.55% for the psychological, situational, and behavioral dimensions respectively, among the mining experts. The Analytical Hierarchy Process (AHP) was used to prioritize all these factors and were validated by experts in Focus Group discussions and a case study conducted at a volunteered Mining Company X in Pahang. Finally, the validated safety culture framework consists of psychological (5 factors), situational (10 factors), and behavioral (9 factors) dimensions. Safety Attitude, (ii) Leadership, (iii) Enforcement on Safety Rules, (iv) Safety Awareness, as well as (v) Reward and Punishment were recognized as the top five of critical factors for safety culture framework in mining industry in Malaysia. In conclusion, it is hoped that the safety culture framework can benefit the mining industry and become one of the solutions for preventing mine accidents in Malaysia.